Effect of short-Term ozone treatments on tomato (Solanum lycopersicum L.) fruit quality and cell wall degradation - Rodoni, Luis Maria (2010)
We evaluated the effect of short-term gaseous ozone treatment (10 μL/L; 10 min) on tomato fruit quality and cell wall degradation. The treatments did not modify fruit color, sugar content, acidity, or antioxidant capacity but reduced fruit damage and weight loss and induced the accumulation of phenolic compounds. In addition, softening was delayed in ozone-treated fruit. Cell wall analysis showed that exposure to ozone decreased pectin but not hemicellulose solubilization. Polyuronide depolymerization was also reduced in ozone-treated fruit. While the treatments did not alter the activity of the pectin-degrading enzymes polygalacturonase (PG) and β-Galactosidase (β-GaI), a clear decrease In pectin methyl esterase (PME) was found. Results show that short-term ozone treatments might be useful to reduce fruit damage and excessive softening, two of the main factors limiting tomato postharvest life, without negatively affecting other quality attributes. The impact of the treatments on fruit softening might be associated with reduced disassembly (solubilization and depolymerization) of pectic polysaccharides.